Toolkit of Competitiveness Strategic Planning - Терехин, Вадим Анатольевич; Козлова, Елена Владимировна (Современная экономика: проблемы и решения, 2015)
In article the detailed analysis of model of formation of the strategic plan of the Harward group with reference to increase of competitiveness of production is given. The effective ways raising level of competitiveness of production of the industrial enterprises through the mechanism of strategic planning are offered. The put forward strategy of increase of competitiveness of the industrial enterprises considers factors of the external and internal environment of the enterprise, assuming the complex, rigid system analysis.